The Determinants of Infant Mortality in Neonatal Period (KEMAS: Jurnal Kesehatan Masyarakat, 2016)
Neonatal mortality is mortality happening to newborn baby who are alive during the birth but died after first month of life (28 days after being delivered). This study used data  from 2013 reports. The aim of this study was to identify determinants of neonatal mortality risk. Case control design was used. Population of cases were newborn baabybies who dying within 28 days after the birth, while the population of controls were newborn baby who do not die within 28 days, selected from the same population of cases. Cases and controls proportion were 1:3 with 39 babies served as cases and 117 babies as controls. Cases were identified form The Health Office and PHC reports, meanwhile controls were selected from neighbor of cases. Univariate, bivariate and multivariate analysis were conducted in this study. The results shows that newborn weight (p=0,03), immediately breastfeeding (p=0,00) and postnatal care (p=0,00) are the risk factors for neonatal mortality.